Multiobjective Optimization Design for Skew and Sweep Parameters of Two-Stage Blades of Axial Fan. (23rd June 2013) - Yue, Wen-hui; Jin, Yong-ping; Wen, Ze-jun
Abstract : Computer aided design and numerical simulation have been widely applied in optimization design of fan blades. In this paper, skew and sweep parameters of two-stage blades of an axial fan are optimized by using the particle swarm optimization algorithm. First, the skew and sweep parameters of two-stage blades of an axial fan are defined. Second, response surface methodology is used to study the relationship between the skew and sweep parameters of two-stage blades and the total pressure and the efficiency of the axial fan. The response surface model that describes the relationship between the skew and sweep of two-stage blades and the total pressure and the efficiency of the axial fan is established. Finally, with the skew and sweep of two-stage blades being design variables and the total pressure and the efficiency being the objectives, a particle swarm optimization algorithm is developed to solve this complex multiobjective optimization problem. The optimal result shows that the total pressure increases by 49.1 Pa and the efficiency increases by 1.55%. In addition, the aerodynamic performance of the axial fan is improved. This research has significance to optimization design of the axial fan.